Regional in-situ stresses in mine design - I. W. Farmer (The Institute of Materials, Minerals and Mining, 1905)
High horizontal stresses and high horizontal to vertical in-situ principal stress ratios in the plane of underground drifts and entries can damage weakly laminated roof rocks quite severely. Such stresses are difficult to measure accurately, as illustrated by case histories of in-situ stress measurement at Wistow and Lea Hall mines, in the UK. Their direction and relative magnitude can, however, be estimated from the absolute velocity vectors of continental plates. With the preliminary results from the World Stress Map project now available it is possible to indicate mining areas where regional horizontal stresses are low, such as Europe, and high, such as Australia and Asia